Traffic Performance Analysis – Emp And Saturation Degrees Using Pkji 2023 - Asan Beni Tokan, Muhamad Muhasiran; Pua Ngajo, Zulfikar; Arjuna Temaluru, Arnoldus; Sutrisno, Widarto; Sekar Langit Wahyu Gutama, Detha (Winter Journal: IMWI Student Research Journal, 2023)
The intersection of KH Wahid Hasyim Road and Inspection Road which is located in the Selokan Mataram, Dabag, Condongcatur, Sleman, DIY area has a high traffic volume because it is a link between residential, educational and economic zones and shopping centers. The problem that often occurs at the intersection of Jalan KH Wahid Hasyim and Jalan Inspection Selokan Mataram, Dabag, Condongcatur, Sleman, DIY is high traffic flow, which often results in traffic jams. The regulation of traffic lights currently in operation cannot overcome the congestion that often occurs, especially during peak hours. The aim of this research is to analyze the performance of signalized intersections using the PKJI 2023 method. To provide appropriate solutions and alternative problem solving at these intersections. Which can improve the performance of the signalized intersection Jl. KH Wahid Hasyim and Jl. Mataram Selokam Inspection. Based on the results of research that has been carried out, it is as follows: a. The traffic flow at the intersection of four is marked KH. Wahid Hasyim and the Mataram Sewer Inspection Road based on the analysis results show that the traffic volume at signalized intersections for 7 days is 16,527 PCU/hour. b. The traffic volume at the intersection with the KH road signal. Wahid Hasyim and the Mataram Sewer Inspection road at peak hours on Monday 02/10/2023, namely 2539 or 1106.2 SMP/Hour. c. Annual average daily traffic at the intersection of four with the KH road signal. Wahid Hasyim and the Mataram Sewer Inspection road for 7 days were taken at peak hours 06.00 – 07.00 and 16.30 – 17.30. get results, namely 45.10 Kend/Hour. d. Calculation of traffic performance and EMP. Which was carried out for 7 days with a K value of 0.08. according to the road width of 6m, you get a result of 3.60 SMP/hour. e. Degree of Saturation at the intersection of four signalized roads KH. Wahid Hasyim in the peak volume period Monday 02/10/2023. Taken at each intersection, North 0.520 SMP/hour, South 0.641 SMP/hour, East 0.162 SMP/hour and West 0.291 SMP/hour. 1. Degree of saturation at the intersection of four KH roads. Wahid Hasyim and the Mataram Sewer Inspection road for the period Monday 10/02/2023 is North 0.520 SMP/Hour, South 0.641 SMP/Hour, East 0.162 SMP/Hour and West 0.291 SMP/Hour. then the service level is D with unstable flow conditions but the speed and movement of vehicles is very low. 2. Vehicle volume based on the results of a 7-day traffic survey shows the number of heavy vehicles on Monday 02/10/2023 for the time period 06.00 – 07.00 and 16.30 – 17.30. namely 2539 Kend/Hour. 3. The capacity value (C) obtained is 2688 SMP/Hour. 4. The value of traffic flow and EMP passing through the four signalized intersections on Jl. KH. Wahid Hasyim and Jl. Sewer Inspection with a K value of 0.08 gets a result of 3.60 SMP/Hour.